EFEKTIVITAS PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP DI KANTOR PERTANAHAN KOTA PEKANBARU - Jefri Fujima Sianturi; Harapan Tua Ricky Freddy Simanjuntak (Universitas Halu Oleo, 2022)
The government is trying to find a way in terms of data collection that is evenly distributed throughout Indonesia so that conflicts do not occur. thereby creating a Complete Systematic Land Registration Program (PTSL). The program was created with the aim of accelerating the provision of legal certainty and legal protection of community land rights in a definite, simple, fast, smooth, safe, fair, equitable and open and accountable manner, so as to improve the welfare and prosperity of the community and the country's economy, as well as reduce and prevent land disputes and conflicts. In addition to a thorough land mapping, this program provides free land certificates to the community. The method in this study uses a qualitative research method with a descriptive approach. The results of the study indicate that the Complete Systematic Land Registration Program in Pekanbaru City has not been realized effectively due to the untimely implementation of the program, the lack of appropriate program measurements and the absence of appropriate program targets in the Complete Systematic Land Registration Program in Pekanbaru City. This is caused by several inhibiting factors including: Human Resources, Facilities and Infrastructure, the network during the program implementation process.